Adaptation and training of rural workers for industrial work : co-ordination of research - Barbichon, Guy; Organisation for Economic Co-operation and Development ([Paris] : Organisation for Economic Co-operation and Development, 1962)
The conference organized by the European Productivity Agency in September 1960 and subsequent meetings arranged by the Organization for Economic Cooperation and Development gave the representatives of workers, employers, administrators, and research workers of many European countries the opportunity to exchange information on the knowledge acquired and the studies underway on the movement of rural workers to industry. Mobility of agricultural manpower is an important facet of the problem of general mobility of the total active population in the course of economic development. On the one hand, mobility is desirable in order to reduce the degree of under-employment in agriculture and, on the other hand, the growth of non-agricultural enterprise needs to draw upon the agricultural population for a supply of labor. To improve economic conditions the concurrent development of both the agricultural and non-agricultural sectors of the economy and agricultural policy must be closely integrated with general economic policy. The appendixes include national bibliographical references and summaries of national research on the problems of adaptation and training of rural workers in Germany, France, Italy, Norway, The Netherlands, and Sweden, and project proposals for international research on the topic. (HC)
Availability: OECD Publication Center, Suite 1305, 1750 Pennsylvania Avenue, Washington, D.C. 20006 ($1.25).
Microfiche.
Keywords: Rural-urban migration -- Europe; Occupational retraining--Europe